Rare Retroperitoneal Cystic Lesions Causing Diagnostic Dilemma – A Case Series - Kaushik Bhattacharya; Sharad Syangden; Mahesh Kumar; Joe Nepram; Kiratpal Singh Brar; Jashanpreet Singh; Ghaiyoor Ahamad; Diwakar Kumar (National Board of Examinations Journal of Medical Sciences, 2023)
Retroperitoneal cystic tumours often cause a diagnostic dilemma and present several clinical challenges because of their rarity, relative late presentation, anatomical location, close relationship with several vital structures in the retroperitoneal space and the surgical expertise required for the management. We present three challenging retroperitoneal cystic space occupying lesions – hydatid cyst, dermoid cyst, and cystic lymphangioma. All 3 cases underwent surgery after initial diagnostic difficulty and had smooth postoperative recovery. Retroperitoneal cyst needs surgical expertise for complete excision which is often difficult due to neighbouring important vital anatomical structures.